2023
DOI: 10.3389/fphys.2023.1203472
|View full text |Cite
|
Sign up to set email alerts
|

Hematological alterations associated with long COVID-19

Abstract: Long COVID-19 is a condition characterized by persistent symptoms lasting beyond the acute phase of COVID-19. Long COVID-19 produces diverse symptomatology and can impact organs and systems, including the hematological system. Several studies have reported, in COVID-19 patients, hematological abnormalities. Most of these alterations are associated with a higher risk of severe disease and poor outcomes. This literature review identified studies reporting hematological parameters in individuals with Long COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 99 publications
(149 reference statements)
1
12
0
Order By: Relevance
“…It is worth noting that previous studies have reported contradictory findings regarding ferritin, which could be attributed to the timing of marker evaluations in relation to the acute phase of the disease. Nevertheless, understanding this issue highlights the need for further studies [ 32 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous studies have reported contradictory findings regarding ferritin, which could be attributed to the timing of marker evaluations in relation to the acute phase of the disease. Nevertheless, understanding this issue highlights the need for further studies [ 32 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous studies have reported contradictory ndings regarding ferritin, which could be attributed to the timing of marker evaluations in relation to the acute phase of the disease. Nevertheless, understanding this issue highlights the need for further studies [27,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, caused by the SARS-CoV-2 virus, is primarily a respiratory disease but can also affect other organ systems, such as the hematological compartment. Several studies reported an increase in white blood cell count, a decrease in red blood cell (RBCs) count and hemoglobin level, an increase in ferritin and D-dimer levels and other clotting markers 1 2 3 4 . Symptoms of COVID-19 vary from mild to severe and may include fever, cough, shortness of breath, fatigue, diffuse body pain, loss of taste or smell, and sore throat 2 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported an increase in white blood cell count, a decrease in red blood cell (RBCs) count and hemoglobin level, an increase in ferritin and D-dimer levels and other clotting markers 1 2 3 4 . Symptoms of COVID-19 vary from mild to severe and may include fever, cough, shortness of breath, fatigue, diffuse body pain, loss of taste or smell, and sore throat 2 3 . In approximately 6–35% of all COVID-19 patients, these symptoms can persist for months after the initial infection with SARS-CoV-2 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation